Effective use of the built environment to manage behavioural and psychological symptoms of dementia: a systematic review. - Lesley J J Soril; Laura E Leggett; Diane L Lorenzetti; James Silvius; Duncan Robertson; Lynne Mansell; Jayna Holroyd-Leduc; Tom W Noseworthy; Fiona M Clement (PLoS ONE)
Objective To determine the effectiveness of built environment interventions in managing behavioural and psychological symptoms of dementia (BPSD) among residents in long-term care settings. Methods Systematic review of literature published from 1995-2013. Studies were included if they: were randomized controlled trials, quasi-experimental trials, or comparative cohort studies; were in long-term or specialized dementia care; included residents with dementia and BPSD; and examined effectiveness of a built environment intervention on frequency and/or severity of BPSD. Quality of included studies was assessed using the Downs and Black Checklist. Study design, patient population, intervention, and outcomes were extracted and narratively synthesized. Results Five low to moderate quality studies were included. Three categories of interventions were identified: change/redesign of existing physical space, addition of physical objects to environment, and type of living environment. One of the two studies that examined change/redesign of physical spaces reported improvements in BPSD. The addition of physical objects to an existing environment (n = 1) resulted in no difference in BPSD between treatment and control groups. The two studies that examined relocation to a novel living environment reported decreased or no difference in the severity and/or frequency of BPSD post-intervention. No studies reported worsening of BPSD following a built environment intervention. Conclusions The range of built environment interventions is broad, as is the complex and multi-dimensional nature of BPSD. There is inconclusive evidence to suggest a built environment intervention which is clinically superior in long-term care settings. Further high-quality methodological and experimental studies are required to demonstrate the feasibility and effectiveness of such interventions.